Automated food attendance robot - Nur Izzati, Abdullah (2007)
This project presents the design and development of a robot from disposal raw material, name automated food attendance robot. The function of the robot is to deliver a food to unable people especially patient in hospital and old folk’s home from pantry to their bed with just pressing a start button. This robot will follow the line tracking which is black in colour. To sense the line, three sensors are used to detect right, center and left line. This project consists of two parts which are software and hardware development. The software development involved the programming for PIC 16f877 microcontroller. Melab programmer and Microcode studio are used for this purpose. Since the raw material that used is mostly aluminum, riveting process is used to build up the body of the robot. After few experiment done, the project is not fully succeeded because of the mistakes in choosing the material as will be discussed in this thesis.